Persepsi Siswa tentang Kompetensi Profesional Guru Hubungannya dengan Motivasi Belajar Mereka pada Mata Pelajaran PAI di Masa Pandemi Covid-19 - Aan Hasanah; Cecep Anwar; Aldi Ripaldi (Gunung Djati Conference Series, 2022)
This study aims to determine the relationship between students' perceptions of professional teacher competence and their learning motivation during the COVID-19 pandemic in PAI subjects in class XII IPA SMAN 5 Bandung. This study uses a quantitative approach with descriptive methods and ex-postfacto research model. While the data collection techniques through observation, interviews, questionnaires and literature study. The data analysis uses a statistical approach with four approaches, namely partial analysis, normality test, correlative test, and Pearson's product moment. From the research results obtained: (1) students' perceptions of the professional competence of teachers are included in the high category with an average score of all indicators of the X variable, which is 3.96 which is in the interval 3.51-4.50; (2) their learning motivation in PAI subjects during the covid-19 pandemic was in the very high category with an average score of all Y variable indicators, which was 3.70 which was at an interval of 3.51-4.50; (3) the correlation of the two variables is 0.36, while the degree of freedom of the influence of the X variable on the Y variable is 10%. Thus there are still 90% of other factors that affect their learning motivation.